Ethical and Legal Manifestations of Informed Consent - Kalina, Peter (Technium Social Sciences Journal, 2020)
Informed consent to medical or surgical treatment, or "permission granted in the knowledge of the possible consequences” is an important, and sometimes contentious and controversial component of clinical practice. From an ethical, legal and philosophical perspective; informed consent has significant implications for health care providers. The three principal elements of informed consent are 1) thorough presentation of information, 2) patient’s capacity to comprehend (competence), 3) patient’s voluntary willingness to undergo or refuse treatment. The history of informed consent is highlighted by precedent-setting legal cases, the atrocities of World War II and subsequent 1947 Nuremberg Trials and, current HIPAA regulations and guidelines. Informed consent involves shared decision-making between provider and patient. Including patients acknowledges and safeguards patient autonomy such that health care decisions are made based on respecting individual preferences, goals, values, beliefs, objectives, and desires. Providers act as advocates for patients' rights. These are fundamental premises of today’s patient-centered care.